Sources of unsafe primary care for older adults: a mixed-methods analysis of patient safety incident reports. (11th April 2017) - Cooper, Alison; Edwards, Adrian; Williams, Huw; Evans, Huw P.; Avery, Anthony; Hibbert, Peter; Makeham, Meredith; Sheikh, Aziz; J. Donaldson, Liam; Carson-Stevens, Andrew
Abstract: Background: older adults are frequent users of primary healthcare services, but are at increased risk of healthcare-related harm in this setting. Objectives: to describe the factors associated with actual or potential harm to patients aged 65 years and older, treated in primary care, to identify action to produce safer care. Design and Setting: a cross-sectional mixed-methods analysis of a national (England and Wales) database of patient safety incident reports from 2005 to 2013. Subjects: 1, 591 primary care patient safety incident reports regarding patients aged 65 years and older. Methods: we developed a classification system for the analysis of patient safety incident reports to describe: the incident and preceding chain of incidents; other contributory factors; and patient harm outcome. We combined findings from exploratory descriptive and thematic analyses to identify key sources of unsafe care. Results: the main sources of unsafe care in our weighted sample were due to: medication-related incidents e.g. prescribing, dispensing and administering ( n = 486, 31%; 15% serious patient harm); communication-related incidents e.g. incomplete or non-transfer of information across care boundaries ( n = 390, 25%; 12% serious patient harm); and clinical decision-making incidents which led to the most serious patient harm outcomes ( n = 203, 13%; 41% serious patient harm). Conclusion: priority areas for further research to determine the burden and preventability of unsafe primary care for older adults, include: the timely electronic tools for prescribing, dispensing and administering medication in the community; electronic transfer of information between healthcare settings; and, better clinical decision-making support and guidance.